2020
DOI: 10.2147/copd.s234823
|View full text |Cite
|
Sign up to set email alerts
|

<p>Impact of Single Combination Inhaler versus Multiple Inhalers to Deliver the Same Medications for Patients with Asthma or COPD: A Systematic Literature Review</p>

Abstract: With increasing choice of medications and devices for asthma and chronic obstructive pulmonary disease (COPD) treatment, comparative evidence may inform treatment decisions. This systematic literature review assessed clinical and economic evidence for using a single combination inhaler versus multiple inhalers to deliver the same medication for patients with asthma or COPD. In 2016, Embase, PubMed and the Cochrane library were searched for publications reporting studies in asthma or COPD comparing a single-inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 49 publications
5
44
1
3
Order By: Relevance
“…Triple therapy with inhaled corticosteroid (ICS), long-acting β 2 -agonist (LABA) and long-acting muscarinic antagonist (LAMA) for COPD has traditionally required use of multiple inhalers, sometimes several times per day [ 1 ]. However, patients’ persistence and adherence with COPD medication administered via multiple inhalers have been shown to be worse than with therapy administered via a single inhaler [ 2 , 3 ]. Reducing the number of inhalers required and frequency of use should improve treatment persistence and adherence, which could in turn improve clinical effectiveness and patient outcomes [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Triple therapy with inhaled corticosteroid (ICS), long-acting β 2 -agonist (LABA) and long-acting muscarinic antagonist (LAMA) for COPD has traditionally required use of multiple inhalers, sometimes several times per day [ 1 ]. However, patients’ persistence and adherence with COPD medication administered via multiple inhalers have been shown to be worse than with therapy administered via a single inhaler [ 2 , 3 ]. Reducing the number of inhalers required and frequency of use should improve treatment persistence and adherence, which could in turn improve clinical effectiveness and patient outcomes [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, previous research has shown that COPD patients have a lower rate of adherence to treatment with multiple-inhaler therapy than single-inhaler therapy [ 32 , 33 ]. Single-inhaler therapy is simpler and thus may lead to better compliance and improved clinical outcomes in COPD patients [ 34 ] and therefore decrease healthcare resource utilization [ 7 , 35 ]. If these outcomes are achieved without increasing costs, this may reduce the economic and healthcare resource burden [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Global Initiative for Obstructive Lung Disease (GOLD) management strategy recommends using ICS/LABA + LAMA in patients with persistent breathlessness, exercise limitation or persistent exacerbation, but it does not specify when to use single-inhaler triple therapy [ 4 ]. Single-inhaler triple therapy may be of benefit in patients with COPD by decreasing inhaler errors, improving adherence rates, and decreasing healthcare costs [ 5 7 ]. In some RCTs comparing triple therapy with dual therapy in COPD, there might be a bias resulting from the use of multiple inhaler devices.…”
Section: Introductionmentioning
confidence: 99%
“…80 Compared with single-inhaler use, the use of multiple inhalers has been shown to be associated with poorer persistence and adherence to COPD medication, which could, in turn, lead to poor symptom control, higher healthcare utilization and costs, and reductions in healthrelated quality of life. [82][83][84][85] The randomized, Phase IV effectiveness INTREPID study (NCT03467425) provides supporting evidence for the benefits of single-versus multiple-inhaler triple therapy. 86 The study evaluated SITT with FF/UMEC/VI versus multiple-inhaler triple therapy as a class over 24 weeks, in 3092 patients with symptomatic COPD and a history of exacerbations who were already receiving triple therapy or had a documented clinical indication for escalation from dual to triple therapy.…”
Section: Dovepressmentioning
confidence: 99%